2015
DOI: 10.2105/ajph.2014.302291
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Savings-Led Microfinance Intervention to Reduce Sexual Risk for HIV Among Women Engaged in Sex Work: A Randomized Clinical Trial

Abstract: Findings advance the HIV prevention repertoire for women, demonstrating that risk reduction may be achieved through a structural intervention that relies on asset building, including savings, and alternatives to income from sex work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 33 publications
(31 reference statements)
9
86
0
Order By: Relevance
“…Data from this paper come from a randomized trial that was implemented from 2011 to 2013 in Ulaanbaatar, Mongolia with 107 women engaged in street-based sex work [27]. The current study took place as part of a parent study testing the efficacy of adding a microfinance component following an HIV risk reduction intervention on women’s sexual risk and economic dependence upon sex work.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from this paper come from a randomized trial that was implemented from 2011 to 2013 in Ulaanbaatar, Mongolia with 107 women engaged in street-based sex work [27]. The current study took place as part of a parent study testing the efficacy of adding a microfinance component following an HIV risk reduction intervention on women’s sexual risk and economic dependence upon sex work.…”
Section: Methodsmentioning
confidence: 99%
“…1. The parent study found the combined HIVSRR and microsavings intervention to be effective in reducing sexual risk [27] and reducing women’s economic dependence upon sex work [28]. Although the microsavings intervention was not originally targeted to reduce violence, the study team hypothesized that a reduction in paying partner violence would be observed in the treatment group since the microsavings intervention appeared to be effective in helping women transfer some of their income from sex work to other sources [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed study methods and procedures for the main trial are described elsewhere (Tsai et al, 2015; Witte et al, 2015). Outcomes of the parent study included reductions in sexual risk behaviors (as measured by self-reported number of unprotected acts of vaginal intercourse) and in proportion of income from sex work (as measured by income from sex work in the past 90 days divided by all income).…”
Section: Methodsmentioning
confidence: 99%
“…Between 2012 and 2017, despite the need for its benefits, DEBI implementation remained limited (Durlak and DuPre, 2008; National Institutes of Health, 2006; Norton et al, 2009; Tinkle et al, 2013; Witte et al, 2015). The HIV-prevention field was experiencing shifts in scientific priorities based on changing global health policies and economics.…”
Section: Case Illustrationmentioning
confidence: 99%